Biochemical spectroscopy - Sauer, Kenneth, 1931- (Methods in enzymology, 1995)
This volume includes spectroscopic methods for the characterization of macromolecules. Methods span the electromagnetic spectrum from X-ray to microwaves. It focuses on the types of information that can be derived: how measurements are made; state of the art apparatus; data acquisition, analysis, and interpretation; casebook examples; and new developments and future directions. Key Features * Ultraviolet and Visible Spectroscopy, including * Absorption and Circular Dichroism * Transient Absorption and Kinetics * Linear Dichroism and Fluorescence * Vibrational Spectroscopy * Magnetic Resonance Spectroscopy * X-Ray Spectroscopy.